Enhancing time resolution by stabilized inverse filter and q estimated on instantaneous spectra (2014)
Physical phenomena, such as attenuation of high frequency components and velocity dispersion, deteriorate seismic images. To enhance seismic resolution, Q filtering is usually applied, where the accurate estimation of Q is the core of this approach. The Matching Pursuit (MP) approach is an instantaneous spectral analysis method that overcomes windowing problems caused by decomposing a seismic trace, providing a frequency spectrum for each time sample of the trace. By changing variables, the spectra is transformed into a new domain where Q is accurately measured. This value is input to a stable inverse Q filter, which solely compensates for the amplitude without distorting the phase, and as a result, an improved time-resolution image is obtained. MP, windowed Fourier (WF), and Gabor transforms (GT) were tested on synthetic seismograms providing Q values that indicated the best performance of MP. Applied to a migrated offshore Colombian seismic line, the entire procedure coded in Matlab compensated for the energy losses and increased the S/N ratio. The trace-by-trace approach guarantees the reliability of the improvement in the continuity of seismic events and is applicable to pre-stack data as well. ResumenLos fenómenos físicos de atenuación de los componentes de alta frecuencia y dispersión por velocidad de fase deterioran la imagen sísmica. Para incrementar la resolución sísmica usualmente se aplican filtros Q inversos, por lo que la estimación precisa del factor de calidad Q es el problema central de este método. El “Matching Pursuit” (MP) es un método de análisis espectral instantáneo que supera los problemas generados al usar ventanas para descomponer una traza, generando un espectro de frecuencia por cada muestra de la traza. Mediante un cambio de variables el espectro se transforma a un nuevo dominio donde se estima Q con precisión. Éste valor se alimenta a un filtro Q inverso estabilizado, el cual compensa solamente la amplitud sin distorsionar la fase obteniendo como resultado se logra una imagen con mejor resolución. Los métodos de MP, transformada de Fourier con ventanas y transformada de Gabor se ensayaron con datos sintéticos suministrando valores de Q que señalaban el mejor desempeño de MP. El proceso completo fue codificado en Matlab y aplicado a una sección marina Colombiana migrada, compensando la perdida de energía e incrementando la relación señal/ruido. El enfoque de traza por traza garantiza la confianza en el realce de la continuidad de los eventos sísmicos, siendo aplicable a datos pre-apilados.